Associative Social Processes Between Malay and Banjar Ethnicities in the Coastal Region of Serdang Bedagai Regency - Fadhil Pahlevi Hidayat; Ishommudin Ishommudin; Akhsanul In'am; Akrim Akrim (International Journal Reglement & Society (IJRS), 2023)
Associative Social Process is part of social interaction that discusses harmony between one ethnicity and another. In this study, ethnic Malays and ethnic Banjar in Pematang Guntung Village can live side by side and are good neighbors with one another. The harmony of the Malay and Banjar ethnic groups is also embodied in the philosophy of outlook on life in society in various fields of life such as socio-economic values, the environment, and so on. This phenomenon is of interest to researchers because the Coastal Malay and Banjar ethnic groups in Pematang Guntung Village have long lived in harmony and side by side in an area. Bearing in mind, existing ethnic differences, and customs, tend to cause inter-ethnic conflict between each group which can annihilate other groups